Teks al-Qur’an dalam Pandangan Nashr Hamid Abu Zayd - Ahmad Fauzan (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2015)
A thought to have an important role to someone. If true thinking it will affect a good understanding leads to attitudes and behavior. However, if the faulty thinking that very result in the destruction of the attitudes and behavior and may even lead to the destruction of one’s Islamic faith. For a Muslim, thinking of concepts related to faith must rely on the descriptions that have been described by Allah SWT and His Messenger and do not necessary diligence in achieving it as the judge actions in fiqh. Because the truth related to faith is not what will go in or unreasonable, scientific or unscientific. But the truth of faith is related to what are established Allah SWT and His Messenger, although not satisfying logic and can not sensed. Related to the above, this paper tries to explain an example of a false thought linked to al-Qur’an faith brought by a prominent modernist Islamic thinker, Nasr Hamid Abu Zaid. Because, to know the truth can sometimes be achieved after knowing a falsehood.